663 QUANTITATIVE PERFUSION ASSESSMENT TO PREDICT ANASTOMOTIC LEAK AFTER ESOPHAGECTOMY. (17th September 2021) - Ishikawa, Yoshitaka; Breuler, Christopher; Chang, Andrew C; Lin, Jules; Orringer, Mark B; Lynch, William R; Lagisetty, Kiran H; Wakeam, Elliot; Reddy, Rishindra M
Abstract:  : Impaired gastric conduit perfusion is a risk factor for anastomotic leak after esophagectomy. Most studies evaluating conduit perfusion have been qualitative with limited impact on post-operative care. The aim of this study is to evaluate the feasibility of intraoperative quantitative assessment of gastric conduit perfusion with indocyanine green (ICG) fluorescence angiography as a predictor for cervical esophagogastric anastomotic (CEGA) leak after esophagectomy. Methods: ICG fluorescence angiography using the SPY elite® (Stryker, MI, USA) system was performed in patients who had undergone a transhiatal or McKeown esophagectomy CEGA from July 2015 through December 2020. Fluorescence angiography assessed Ingress (dye uptake) and Egress (dye exit). Ingress Index, Ingress Time, Egress Index, and Egress Time at two anatomic landmarks (tip of the conduit, and 5 cm from tip) were calculated from the measured curve of fluorescence (Figure). The collected data between the leak (L) group and the no-leak (NL) group were compared by both univariate and multivariable analyses to analyze risk factors potentially associated with CEGA leak. Results: 304 patients were evaluated. There was no significant difference in patients' demographic and post-operative complications between the groups (L n = 73; NL n = 231), except for anastomotic stricture (42.5 vs 9.1%, p < 0.01). 5 cm and Tip Ingress Index were significantly lower in L (35.0 vs 45.1% and 17.4 vs 25.7%, p < 0.01). 5 cm Ingress Time was significantly higher in L (70.6 vs 56.8 sec, p < 0.01). On multivariable analysis, these variables retained statistical significance, suggesting that these three variables can be used to predict future leak. Conclusion: This study revealed that gastric conduit perfusion correlates with the incidence of CEGA leak. Intraoperative measurement of gastric conduit perfusion may be predictive for CEGA leak following esophagectomy. These variables can be easily collected intraoperatively with the SPY study and used to make clinical decisions which may avert CEGA leak.